Oral Manifestations and Clinical Management of Coccidioidomycosis: A Systematic Review - , Expedito Sérgio Barroso de Carvalho; , Tullyo Sarmento Magalhães; , Maria Tayara Marques de Freitas; , Pedro Isac Fontenele Saldanha; , Guilherme Mendes Prado (Archives of Current Research International, 2025)
Introduction: Coccidioidomycosis is a systemic fungal infection caused by Coccidioides immitis and C. posadasii, transmitted through the inhalation of arthroconidia from the soil. It predominates in arid regions of the Americas, including Brazil. Although it primarily affects the lungs, it can manifest in the oral cavity, causing lesions such as ulcers, nodules, and verrucous plaques, often mistaken for other oral diseases. Methodology: The systematic literature search was conducted in January 2025 in the databases PubMed, Web of Science, and LILACS, included studies were those published in Portuguese and English from 1964 to 2024, and case reports relating coccidioidomycosis to the oral cavity. Diagnosis requires clinical examination, epidemiological history, and laboratory tests, including biopsy, serology, and PCR. Treatment is based on antifungal agents such as fluconazole and itraconazole, with amphotericin B used in severe cases. Diabetic patients are more vulnerable to infection. This literature review analyzed studies, identifying two relevant cases. Results: The research highlighted the importance of early diagnosis and individualized treatment management. Additionally, awareness and prevention are essential, especially in endemic areas. The relationship between diabetes and coccidioidomycosis reinforces the need for an integrated clinical approach. Early recognition of these lesions significantly influenced therapeutic decision-making and improved clinical outcomes, highlighting their prognostic value. Conclusion: Further studies are needed to enhance the understanding of the disease, its diagnosis, and therapeutic approach, with a focus on oral manifestations. Emphasizing the importance of early diagnosis through oral findings can lead to timely treatment and better patient prognosis.